Some Issues in Modeling and Forecasting Inflation in South Africa. - Aron, J; Muellbauer, J (CSAE (University of Oxford), 2009)
Inflation targeting central banks will be hampered without good models to assist them to be forward-looking. Many current inflation models fail to forecast turning points adequately, because they miss key underlying long-run influences. The world is on the cusp of a dramatic turning point in inflation. If inflation falls rapidly, such models can underestimate the speed at which interest rates should fall, damaging growth. Our forecasting models for the new measure of producer price inflation suggest methodological lessons, and build in conflicting pressures on SA inflation from exchange rate depreciation, terms of trade shocks, collapsing oil, food and other commodity prices, and other shocks. Our US and SA forecasting models for consumer price inflation underline the methodological points, and suggest the usefulness of thinking about sectoral trends. Finally, we apply the sectoral approach to understanding the monetary policy implications of introducing a new CPI measure in SA that uses imputed rents rather than interest rates to capture housing costs.